Introduction to ground penetrating radar : inverse scattering and data processing - Persico, Raffaele, 1969- (Hoboken, New Jersey : Wiley, IEEE Press, 2014)
'This book presents a comprehensive treatment of ground penetrating radar using both forward and inverse scattering mathematical techniques. Use of field data instead of laboratory data enables readers to envision real-life underground imaging; a full color insert further clarifies understanding. Along with considering the practical problem of achieving interpretable underground images, this book also features significant coverage of the problem's mathematical background. This twofold approach provides a resource that will appeal both to application oriented geologists and testing specialists, and to more research-oriented physicists and engineers'--
Includes bibliographical references (pages 358-364) and index.
Keywords: Ground penetrating radar